1982
DOI: 10.1002/ccd.1810080504
|View full text |Cite
|
Sign up to set email alerts
|

Permanent pacemaker implantation in the cardiac catheterization laboratory: The subclavian vein approach

Abstract: During a 36-month period, 171 permanent pacemaker procedures were performed in the cardiac catheterization laboratory by invasive cardiologists. This included 111 initial pacemaker system implants, via the percutaneous subclavian vein approach, 45 pulse generator changes, and 15 miscellaneous procedures. In no case did subclavian vein puncture result in pneumothorax, hemothorax, or brachial plexus injury. In patients undergoing initial lead placement, the dislodgment rate was 0.8% over a 16-month follow-up per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…However, we found that atrial lead displacement (1.85%) was more likely to occur than ventricular lead displacement (0.46%); this difference reached statistical significance (p < 0.05). Our rates of electrode displacement compare favorably with others reported--l.7% for both atrial and ventricular leads [11] and 0.8% for ventricular leads only [12]. Although Mueller et al [10] reported no significant difference in atrial (1.3%) compared with ventricular (0.9%) lead displacement, their ventricular lead displacement rate was almost twice as high as ours and their atrial lead displacement rate somewhat lower, accounting for the significant difference found in our series.…”
Section: Discussionsupporting
confidence: 89%
“…However, we found that atrial lead displacement (1.85%) was more likely to occur than ventricular lead displacement (0.46%); this difference reached statistical significance (p < 0.05). Our rates of electrode displacement compare favorably with others reported--l.7% for both atrial and ventricular leads [11] and 0.8% for ventricular leads only [12]. Although Mueller et al [10] reported no significant difference in atrial (1.3%) compared with ventricular (0.9%) lead displacement, their ventricular lead displacement rate was almost twice as high as ours and their atrial lead displacement rate somewhat lower, accounting for the significant difference found in our series.…”
Section: Discussionsupporting
confidence: 89%
“…13,14 Early concerns about safety and sterility have been shown to be unfounded when these issues are appropriately addressed prospectively. The unique capabilities from a radiologic point of view are invaluable.…”
Section: Implantation Facility and Equipmentmentioning
confidence: 98%
“…Bereits seit über 20 Jahren werden Studien publiziert, die über nicht signifikant unterschiedliche Komplikationsraten nach chirurgischer Schrittmacher-oder Defibrillatorimplantation in einem Operationssaal im Vergleich zur Durchfüh-rung des Eingriffs durch einen Kardiologen im Elektrophysiologie-oder Herzkatheterlabor berichten (Literaturbeispiele [5,10,12,14,18,19]). Diese Publikationen geben die Erfahrungen einzelner Zentren wieder und können nicht darüber hinwegtäuschen, dass auch höhere Komplikationsraten berichtet wurden (Literaturübersicht in [18]).…”
Section: Personelle Voraussetzungenunclassified